Multiple Attribute Decision-Making (MADM) Method for Material Selection in High Speed Engineering Application - Vilas K. Patil, Udhhav M. Shirsat (International Journal of Advanced Science and Technology, 2020)
Material selection is one of the challenging works in every engineering sector, basically when the strength is criteria for heavy/light duty engineering application. Selection criteria for high speed/high temperature application are different than traditional method. Single element or materials are not fulfilling the mechanical/tribological properties for engineering applications. So fulfill tribological or engineering conditions need to select suitable material by using the combination of different elements is one of the difficult task for engineer or designer. The manufacturing industry frequently faces the problem related with combination of alternative and its weight percentage and selecting best material from various criteria. In this paper, various elements taken from required sources and using its attributes or different properties will used for finalized composite material. Rank these element based on optimization method and select top beneficial elements for preparation of material for such application. The purpose of this work to prepare material from different alternative (elements)by using multi criteria decision making method including SAW,WPM, AHP, TOPSIS, Modified TOPSIS and VIKOR methods for high speed engineering application.